Macroeconomic Policy Analysis on Labor Absorption in the Manufacturing Industry Sector of South Sulawesi - Andi Naila Quin Azsisah Alisyahbana; Retno Fitrianti; Andika Isma; Betania Kertika Muflih (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study examines the determinants of regional economic performance with a particular focus on the roles of democracy and investment as key drivers of economic development in South Sulawesi. Using panel data from 24 districts and municipalities over the 2021–2023 period, this research analyzes how variations in political governance, investment flows, and structural economic characteristics shape regional growth outcomes. The study employs a panel regression approach comparing Pooled OLS, Fixed Effects, and Random Effects models to obtain consistent estimations and identify the most appropriate specification for explaining regional economic dynamics. The analysis highlights the conceptual significance of democracy as an institutional foundation that influences policy effectiveness, government accountability, and stability, all of which contribute to a conducive environment for economic activity. Investment is also positioned as a critical economic instrument that supports productivity, technological diffusion, and industrial upgrading. The findings indicate that the relationship between democracy, investment, and regional economic performance is not uniform across regions, reflecting differences in institutional capacity, labor quality, and industrial structure. Furthermore, the results emphasize that democratic governance and investment inflows operate as complementary forces: improvements in democratic quality can strengthen investor confidence, while investment outcomes can reinforce governance legitimacy by generating economic benefits. This study provides theoretical and empirical insights into how these variables interact in shaping regional development trajectories. The implications of this research underscore the need for region-specific strategies that integrate institutional strengthening, targeted investment policies, and human capital development to achieve sustainable and equitable economic growth.